2012
DOI: 10.4317/medoral.17424
|View full text |Cite
|
Sign up to set email alerts
|

Determination of susceptibility to sensitization to dental materials in atopic and non-atopic patients

Abstract: Introduction: Some studies report that atopic patients have a greater frequency of delayed-type sensitization than non-atopic patients. Objective: To determine the influence of the atopic condition on delayed sensitization to dental materials. Design: cross-sectional study. Methods: Forty (40) atopic subjects and forty (40) non-atopic subjects, of both sexes, between 20 and 65 years of age were included. The determination of delayed sensitization to dental materials was performed using patch test. An oral exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Oral hypersensitivity to dental materials is rare, probably due to some factors such as: the presence of saliva in the mouth, which leads to dilution and facilitates the removal of allergens; keratinization in some areas of the mucosa, hindering the union of the hapten; high local tissue vascularization, enabling the removal of allergens and mechanical resistance of the oral mucosa. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral hypersensitivity to dental materials is rare, probably due to some factors such as: the presence of saliva in the mouth, which leads to dilution and facilitates the removal of allergens; keratinization in some areas of the mucosa, hindering the union of the hapten; high local tissue vascularization, enabling the removal of allergens and mechanical resistance of the oral mucosa. 3 …”
Section: Discussionmentioning
confidence: 99%
“…However the relation between atopy and late hypersensitivity to dental materials had not been analyzed until Alcayaga present a study that, just as our study, showed that atopy condition is not related to the high frequency of positive patch tests for dental materials. 3 …”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of patients sensitized to dental material and the presence of intraoral clinical symptoms (hypersensitivity) cannot be correlated [20]. This suggests the role of the oral mucosa as an important sensitization route, however, showing a high level of tolerance.…”
Section: Case Reportmentioning
confidence: 99%
“…La indicación de test de parche cutáneo con lectura a las 96 horas es lo que habitualmente se utiliza para la detección de respuestas de hipersensibilidad tardía, sin embargo, reacciones retardadas a metales pudiesen ocurrir hasta los 14 días, por lo que algunos centros incluyen la medición a los 7 y 14 días. 18 Endoscopía digestiva: El SBU está asociado ocasionalmente al reflujo gastroesofágico, específicamente con la sintomatología de la orofaringe y base de la lengua. Anecdóticamente, se ha reportado alivio de síntomas del SBU con omeprazol dos veces al día, en pacientes con reflujo gastroesofágico (RGE) demostrado por endoscopia.…”
Section: Introductionunclassified